Correlation between Subfoveal Choroidal Thickness and Anterior Segment Inflammation in Patients with Chronic Stage of Vogt-Koyanagi-Harada Disease. (3rd April 2022) - Ormaechea, Maria Soledad; Hassan, Muhammad; Mahajan, Sarakshi; Nguyen, Quan Dong; Couto, Cristobal; Schlaen, Ariel
ABSTRACT: Purpose: To correlate changes in subfoveal choroidal thickness (SCT) with the degree of anterior inflammatory activity in chronic Vogt-Koyanagi-Harada (VKH) disease. Methods: Anterior segment inflammation was assessed using SUN anterior chamber cell grading criteria, and SCT was measured using EDI-OCT in patients with VKH at multiple visits. ANOVA was used to compare the mean SCT for each anterior chamber cell grade. Regression analysis was used to correlate the anterior segment cell grade and the SCT. Results: 14 patients were included in the study. A total of 432 data points consisting of SCT and anterior segment cell values were analyzed. ANOVA demonstrated significant difference between the mean SCT for different anterior chamber cell grades ( p < .0001). Regression analysis demonstrated significant correlation between SCT and grade of anterior chamber cells (R 2 = 0.37, p < .001). Conclusions: Chronic VKH is characterized by a dynamic change in SCT that correlates with anterior segment inflammatory activity.